Toxicology and Drug Safety Issues: A Review Article - Yilkal, Tariku Belay (In-Vitro-In-Vivo-In-Silico Journal, 2025)
Background Research and drug development industries have multiphase drug screening procedures, which can be debated. As a result, harmful products may still reach for public health service delivery due to vulnerabilities in the process. Main body A wide range of test compounds have delayed manifestation of undesired effect on the study subject, with the time to undesired effects after acute exposure being weeks and months. Acute toxicology in a preclinical trial also has limited clinical value as its lethal dose is the endpoint for a conclusion, and death sometimes occurs after a scheduled period of acute toxicology. Countless resources are wasted, and numerous new drugs are introduced into the pharmaceutical market with assumed safety analysis every year due to vulnerable multi-procedures in preclinical trials. The principal use of collected data from a preclinical trial is to support regulatory categorization and harmful labelling decisions. However, the data can also be used to derive safe use threshold levels, which may lead to the use of unsafe material. The criteria for classification and labelling also differ among countries, sometimes among authorities within the same country. The fundamental concept of toxicology states that ‘all chemical substances are potential poisons depending on the amount and duration of exposure. However, the toxic property of a test compound cannot be created or eliminated by simply the amount administered to study animals. Conclusion All xenobiotics are poisons at any amount with different severity that can be calculated using biological parameters.
Keywords: Drug Safety; Preclinical Trials; Pharmaceutical Research; Toxicology